The effect of empowerment to improve patient safety culture among hospital nurses - Rusdi, Rusdi; Said, Faridah Mohd; Umar, Nur Syazana (International Journal of Public Health Science (IJPHS), 2024)
A decline in the quality of services provided to patients and an increase in patient care costs are caused by a decline in their ability to work. Patient safety culture is a product of individual and group values, attitudes, competencies, and behavioral patterns that determine the commitment, style, and capabilities of a health service organization towards patient safety programs. This study examined the effects of empowerment on patient safety culture and employed descriptive, cross-sectional, analytical methodology. Proportionate random sampling was the sample method used at a hospital in Samarinda, Indonesia, with 119 respondents. Hospital surveys regarding patient safety culture and empowerment were used to gather data. Partial least squares and structural equation modeling were used for data analysis. Regarding opportunity indications for activities, the empowerment average had the highest score, 15.8 (SD=2.987). For teamwork within the unit, the patient safety culture had the highest average score of 13.3 (SD=1.777). The initial sample estimate value of 0.677 indicated that empowerment had a positive impact on patient safety culture. The T-Test result was 15.180, indicating that the value was greater than 1.98. Nurses’ autonomy in their work can be supported through empowerment. The stronger the empowerment, the more patient-safety culture the hospital will have.